(untitled) (Revista Brasileira Multidisciplinar, 2021)
Biomimicry comprehends the search for principles developed by living beings and natural mechanisms for application within the most varied human activities. It can be said that this new science is in the process of development within several areas of research. The study of termite habitats and the ventilation process used by these insects has proven to be a highly feasible alternative, as demonstrated by some constructions developed in Africa and Australia. Therefore, the present work involved the creation of a bioinspired building model in an attempt to apply the principles found in the literature regarding the housing format and the self-cooling process used by termites of the species Cornitermes cumulans, very common in the Brazilian cerrado. This model was inspired by the profile and mechanism of air circulation of the analyzed mounds, involving the elaboration of a three-dimensional project and its subsequent rendering.